2024
DOI: 10.3390/ma17102336
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Addition of Basalt Powder on the Properties of Foamed Geopolymers

Michał Łach,
Barbara Kozub,
Sebastian Bednarz
et al.

Abstract: Geopolymers are binder materials that are produced by a chemical reaction between silica or aluminum compounds with an alkaline activating solution. Foamed geopolymer materials are increasingly being cited as a viable alternative to popular organic insulation materials. Since the foaming process of geopolymers is difficult to control, and any achievements in improving the performance of such materials are extremely beneficial, this paper presents the effect of the addition of basalt powder on the properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A multitude of researchers have demonstrated that incorporating basalt stone into ordinary-weight concrete, as a replacement for sand and gravel, enhances the mechanical and durability properties of the concrete [20][21][22][23][24]. Through extensive laboratory investigations, it has been proven that incorporating basalt stone powder into ordinaryweight concrete contributes to a notable reduction in the porosity of the Interfacial Transition Zone (ITZ) and consequently enhances both the compressive strength and overall durability of the concrete [25][26][27]. Furthermore, experimental investigations have demonstrated the substantial impact of incorporating basalt fibers on enhancing the strength and durability of ordinary-weight concrete [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of researchers have demonstrated that incorporating basalt stone into ordinary-weight concrete, as a replacement for sand and gravel, enhances the mechanical and durability properties of the concrete [20][21][22][23][24]. Through extensive laboratory investigations, it has been proven that incorporating basalt stone powder into ordinaryweight concrete contributes to a notable reduction in the porosity of the Interfacial Transition Zone (ITZ) and consequently enhances both the compressive strength and overall durability of the concrete [25][26][27]. Furthermore, experimental investigations have demonstrated the substantial impact of incorporating basalt fibers on enhancing the strength and durability of ordinary-weight concrete [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%